Do Big 5 Personality Characteristics and Narcissism Predict Engagement in Leader Development? - Blair, Carrie A.; Palmieri, Rachele E.; Paz-Aparicio, Carmen (Frontiers in Psychology, 2018)
This study examines personality as a predictor of engagement behavior displayed during leader development programs. Leader development engagement behavior (LDEB) is measured by collecting self- and director ratings of behaviors displayed by undergraduate students during 1-year leader development programs (e.g., showing interest in a variety of topics, maintaining a positive attitude, arriving prepared for meetings, engaging with peers, and reflecting on development). Results suggest that factors of the Big 5 personality characteristics and the Narcissism Personality Inventory predict engagement behaviors in leader development. Post hoc analysis was conducted to better understand patterns of relationships between Big 5 factors and narcissism with specific LDEBs. Narcissism is negatively correlated with director ratings of reflection on development and engagement with peers. As a result of this research, leader development program directors should consider the benefits and risks of including narcissistic individuals in leader development programs.